Tax, inequality, and human rights - Alston, Philip; Reisch, Nikki (New York, NY : Oxford University Press, 2019)
This book examines why taxation is central to the enjoyment or suppression of human rights in an age of rising nationalism, authoritarianism and disillusionment with the traditional role of the state. Taxation and human rights are at the heart of debates about the appropriate balance in society between the public and private sectors, and ultimately the content of a new social contract.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Taxation -- Law and legislation; Tax administration and procedure; Equality before the law; Taxation -- Social aspects; Tax evasion; Tax protests and appeals; Human rights; Law; Laws of specific jurisdictions & specific areas of law